Monopoly and Accounting: A Fun Way to Learn Financial Management - Beloan, Bertha; Mande, Henni; Da'a, Fitrianti; Rayyani, Wa Ode; Mairi, Marsya Utani; Handayani, Fany Arista; Azzahra , Wa Ode Nayla Fatimah; Satriani , Nilla (PT Inovasi Pratama Internasional, 2025)
Introduction: Strengthening financial literacy among multicultural youth, particularly those without access to formal schooling due to undocumented status, remains an important educational priority. This community engagement program aimed to introduce basic accounting and financial management concepts to children and teenagers at Angkatan Belia Islam, Pulau Pinang, Malaysia, using the Monopoly board game as an engaging learning medium. Methods: The activity involved 28 participants from diverse family backgrounds and nationalities. Conducted on 15 May 2025 at the PERMAI Learning Centre, the program applied a game-based learning approach combined with guided instruction, participatory observation, and short evaluation sheets to assess understanding. Key financial concepts presented included income, expenses, budgeting, cash flow, risk, and simple transaction recording. Results: The use of Monopoly effectively enhanced students’ engagement and comprehension. Participants demonstrated improved ability to recognize types of income and expenses, make basic financial decisions, and relate game scenarios to real-life money management. The activity also fostered collaborative skills such as teamwork, negotiation, and communication. Discussion: Participatory reflection showed that students perceived accounting and financial topics as more enjoyable and accessible when presented through interactive gameplay. Short-term impacts included increased confidence in handling money and a willingness to apply basic budgeting practices in their daily lives. Conclusion: The Monopoly and Accounting program successfully promoted foundational financial literacy among underserved multicultural youth in Malaysia. This model demonstrates a replicable approach to delivering meaningful financial education in community-based, non-formal learning environments.